An Overview of Coastal and Marine Resources and their Management in Sultanate of Oman - CHOUDRI, B.S.; BAAWAIN, Mahad; AHMED, Mushtaque (Journal of Environmental Management and Tourism, 2016)
Coastal areas of Oman are in the focus of intensive tourism, urbanization and other development activities and are subject to changing physical processes causing significant natural environment modifications and such changes have been seen over the past few years. Government of Oman has worked out comprehensive coastal zone management plans towards protection of coral reefs, wetlands, mangrove, turtles and other resources, including land and groundwater resources in order to meet the challenges of environmental protection along with the development. Integrated coastal zone management (ICZM) has result an approach with the government developing legislations for coastal zone protection, management plans, recovery and governance along with awareness raising programs. However, public participation along with capacity building efforts could be increased at all levels; the better it would be for the coast and for posterity. This review also shows that in the past few years, there have been more research and technical studies through projects that have increased scientific knowledge and allowed access to the best techniques and knowledge available at international and national levels. However, knowledge also needed on coastal processes to establish techniques for minimizing risks and climate change adaptation focusing on biotic communities and environmental quality. Further, Omani coastal zone management would benefit from the application of economic valuation techniques and instruments.
Keywords: coastal management; environment; programs; policies; Sultanate of Oman